2015
DOI: 10.1002/ddr.21272
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Aging‐Dependent MicroRNAs in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is the most severe fibrotic lung disease and characterized by the accumulation of (myo)fibroblasts and collagen within the alveolar wall resulting in obliteration of the gas-exchange surface. Although the detailed pathogenesis is not understood, recent studies have found that several microRNAs (miRNAs) are associated with the progression of lung diseases including IPF. IPF is an age-associated disease and, accordingly, frequently found in an aged population. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 121 publications
(129 reference statements)
2
7
0
Order By: Relevance
“…Instead, we found that level of circulating miR-29c-3p decrease in women (healthy controls) after age 50 compared to younger women. Taking into account the anti-fibrotic activity of miR-29, our data are consistent with the fact that fibrotic processes increase with advancing age (Nho, 2015). To evaluate the diagnostic effectiveness of potential markers, we performed a ROC analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Instead, we found that level of circulating miR-29c-3p decrease in women (healthy controls) after age 50 compared to younger women. Taking into account the anti-fibrotic activity of miR-29, our data are consistent with the fact that fibrotic processes increase with advancing age (Nho, 2015). To evaluate the diagnostic effectiveness of potential markers, we performed a ROC analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, over 20 microRNAs including members of the miR-30, let-7, miR-29 families were decreased in IPF and lung cancer, commonly increased microRNAs included miR-155, miR-21, miR-205, and miR-31 ( 101 ). While the cellular origin and exact effects of all of these common microRNA changes are unclear, together with the observations about lung development, microRNA changes in the IPF lung suggest a loss of the differentiated organ regulatory networks potentially as a result of desynchronized aging ( 102 , 103 ).…”
Section: Role Of Non-coding Rnas In Ipfmentioning
confidence: 99%
“…Interestingly, these pathways have been shown to be controlled by miR-200 family members [21]. Y ang et al .…”
Section: Introductionmentioning
confidence: 99%